PELAYANAN DAN PROMOSI DIVISI KLINIK DAN APOTIK PT. DEVA MITRA ABADI - Widarto Widarto; Alimuddin Alimuddin (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2021)
This study aims to determine the extent to which services and promotions have been carried out by the Division of Clinics and Pharmacies at PT. Deva Mitra Abadi and to find out what factors are obstacles in service and promotion and how efforts are being made to overcome these obstacles.This type of research is qualitative with a research focus on service issues and promotion implementation. The data sources are primary data and secondary data. The data collection techniques used are interviews, documentation, and observation. statistical formulas and only describe or describe problems qualitatively, even if there are numerical data, they are only supporting figures from qualitative analysis.The results of the study indicate that the service is carried out through the dimensions of Tangible, Reliability, Reliability, Responsiveness, Guarantee and certainty, and Empathy. direct marketing to conduct sales transactions either through personal media such as mobile phones, washApp, instagram, facebook, email and until now do not have a website. The obstacles that many face in terms of promotional activities are the lack of funds, limited personal selling personnel, do not have cooperation with agencies The government, especially public hospitals and private hospitals, has a strategic location, but it is not yet densely populated so that it is not optimal in disseminating information to the surrounding community. Efforts are being made to overcome this by investing separately for promotion, collaborating advertising activities with other divisions and also advertising tailored to the needs of existing funds and equipping each employee with the ability to become personnel selling.